How we treat patients with lung cancer during the SARS-CoV-2 pandemic: primum non nocere. (15th April 2020) - Banna, Giuseppe; Curioni-Fontecedro, Alessandra; Friedlaender, Alex; Addeo, Alfredo
Abstract : New cases of the novel coronavirus, also known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continue to rise worldwide. A few reports have showed that mortality due to SARS-CoV-2 is higher in elderly patients and other active comorbidities including cancer. To date, no effective treatment has been identified and management for critically ill patients relies on management in intensive care units. Patients with lung cancer are at risk of pulmonary complications from COVID-19. Furthermore, the use of chemotherapy might have a negative impact in patient's outcome. Therefore, the risk/benefit ratio of systemic anticancer treatment (SACT) has to be considered. For each patient, several factors including age and comorbidities, as well as the number of hospital visits for treatment, can influence this risk. Each hospital around the world has issued some internal policy guidelines for oncologists, aiming to limit risks during this difficult time. We hereby propose a tool to support oncologists and physicians in treatment decision for patients with lung cancer. There are several variables to consider, including the extent of the epidemic, the local healthcare structure capacity, the risk of infection to the individual, the status of cancer, patients' comorbidities, age and details of the treatment. Given this heterogeneity, we have based our suggestions bearing in mind some general factors There is not easy, universal solution to oncological care during this crisis and, to complicate matters, the duration of this pandemic is hard to predict. It is important to weigh the impact of each of our decisions in these trying times rather than rely on routine automatisms.